2017
DOI: 10.1159/000471772
|View full text |Cite
|
Sign up to set email alerts
|

Off-Clamp versus On-Clamp Robotic Partial Nephrectomy: A Multicenter Match-Paired Case-Control Study

Abstract: Introduction: The aim of this study was to compare the outcomes of on-clamp and off-clamp robotic partial nephrectomy (RPN). Materials and Methods: The charts of all patients who underwent an RPN at 8 institutions between 2010 and 2014 were retrospectively reviewed. The patients who underwent an off-clamp RPN were matched to on-clamp RPN in a 1-4 fashion according to the following variables: RENAL score, tumor size and surgeon's experience. Pre-, intra-, and postoperative data were compared between both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Thompson et al [21] and others who analyzed functional recovery after PN in solitary kidney concluded that for each minute of ischemia, there was 5-6% increase in the risk of renal function decline [21][22][23]. By contrast, Peyronnet et al [24] were not able to show a direct relationship between ischemia time and postoperative renal function preservation.…”
Section: Discussionmentioning
confidence: 96%
“…Thompson et al [21] and others who analyzed functional recovery after PN in solitary kidney concluded that for each minute of ischemia, there was 5-6% increase in the risk of renal function decline [21][22][23]. By contrast, Peyronnet et al [24] were not able to show a direct relationship between ischemia time and postoperative renal function preservation.…”
Section: Discussionmentioning
confidence: 96%
“…However, the use of arterial clamping (i.e. on‐clamp vs off‐clamp PN) , the use of the early unclamping technique , as well as the approach used (i.e. retroperitoneal vs transperitoneal), were recorded as surrogates of the surgical technique used in each centre.…”
Section: Methodsmentioning
confidence: 99%
“…We included 13 observational studies, in which there was a description of functional and oncologic results in patients undergoing PN without ischemia compared with PN with warm ischemia [ 15 17 18 19 20 21 22 23 24 25 26 27 28 ], and one clinical trial [ 29 ] ( Table 1 ) [ 15 17 18 19 20 21 22 23 24 25 26 27 28 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the other items, the evaluation yielded mostly a low risk of bias ( Fig. 2A, B) [15,[17][18][19][20][21][22][23][24][25][26][27][28]. For Andersen 2019, we found an unclear risk of bias for blinding since there was no clear description of this issue.…”
Section: Evaluation Of the Risk Of Biasmentioning
confidence: 99%